Analysis of Children's Mental Health in Parents of Different Religions: An Anthropological Psychological Perspective - Junida, Dwi Surti (International Journal Ethnic, Racial and Cultural Heritage, 2024)
Based on religious differences between couples pose challenges in parenting, so this study aims to find cultural diversity and parenting in families of other religions, psychological impacts and mental health on children from families of different faiths, and the integration of psychological anthropology in the care of children of families of different religions. This qualitative research explores issues or mental problems experienced by children in forming their character. The study found that parenting families of other faiths has a positive value for their children's development. Parenting practices are based on cultural traditions, ethnic values, and family habits passed down from generation to generation, as well as the influence of parenting on the emotional, social, and cognitive development of children who apply parenting strategies such as authoritative, overprotective, and permissive that do not carry elements of their respective religions. In addition, it also found integration in the care of children through practices such as tolerance, politeness, helpfulness, honesty, friendliness, empathy, and sympathy. The impact of mental health on their parenting can be prevented by implementing inclusive parenting that emphasizes the practice of cultural diversity, values, and beliefs in their family environment. Hopefully, these findings can provide an essential understanding of the religious differences that affect the upbringing of children of different faith families, providing insight for anthropology and psychology practitioners on the importance of understanding aspects of religion in supporting child development.